PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN SENI BUDAYA - Hartini, Hartini; Tryanasari, Dewi; Maruti, Endang Sri (Premiere Educandum, 2015)
The character is a distinctive personality of each individual to live and work,both in the scope of the family, community, nation and state. Arts and culture inelementary school in 2004 as a core curriculum capacity building in the field ofaesthetics has a potential role to support and realize the whole Indonesian humancharacter. This study describes the implementation and building constraints positivecharacter of students in arts and culture in SDN Jogodayuh 1, District Geger, MadisonCounty. This study used a qualitative research design with a phenomenologicalapproach. Triangulation of data is done by using triangulation and triangulationmethods. The results of this study indicate that many of the benefits obtained by thestudents in the study of art and culture in primary schools include: (1) deepenwonderfully flavors, (2) knowledge of the objective and subjective elements, (3)strengthen the love for the arts and culture, (4) foster subtlety of flavor, (5) deepen theculture, (6) assess the work of art, (7) awareness on the negative effects, (8) to strengthenpublic confidence, (9) discipline, and (10) provide extensive insight and provision forspiritual and psychological life.Keywords: character education, elementary school, learning art and culture.